Pulmonary function tests at low altitude predict pulmonary pressure response to short-term high altitude exposure - Yang, Yuanqi; Liu, Chuan; Yu, Shiyong; Qin, Zhexue; Yang, Jie; Bian, Shizhu; Gao, Xubin; Zhang, Jihang; Hu, Mingdong; Wu, Guoming; Ding, Xiaohan; Zhang, Chen; et al. (Respiratory physiology & neurobiology, 2020)
•Travelling to high altitude (HA) presents a risk of the excessive increases in mean pulmonary artery pressure (mPAP), which is associated with impaired exercise capacity and fatal HA pulmonary oedema.•FEF25% at low altitude and smoking were the independent predictors for identifying subjects with mPAP≥30 mmHg at high altitude.•FEF25% at low altitude was linearly correlated with mPAP at high altitude, which mainly existed in smokers.•Subjects with FEF25%<7.55 L/sec at low altitude showed higher levels of mPAP, and total PVR, and a multivariable odds ratios of 11.16 for developing mPAP≥30 mmHg at high altitude than those with FEF25%≥7.55 L/sec at low altitude.•Low FEF25% values at low altitude are susceptible to an excessive increase in mPAP following short-term HA exposure, especially in smokers. Background: Travelling to high altitude (HA) presents a risk of the high levels of pulmonary artery pressure (PAP) at altitude, which is associated with impaired exercise capacity and fatal HA pulmonary oedema. However, prediction of high levels of PAP at altitude is still unclear. Methods: Echocardiography and pulmonary function tests were performed on 121 healthy men at low altitude (LA) and 4100 m (5 ± 2 h after a 7 day ascent). Results: HA exposure increased the levels of FEV1/FVC ratio, FEF25%, 50%, 75%, MMEF, mPAP, total pulmonary vascular resistance (PVR) and systolic pulmonary arterial pressure (SPAP). More smokers and lower forced expiratory flow at 25% of forced vital capacity (FEF25%) at LA were observed in subjects with mPAP≥30 mmHg than those with mPAP<30 mmHg at HA. Multivariate logistic regression identified that FEF25% at LA [odds ratio (OR) 0.50, 95%CI 0.33−0.76, p = 0.001] and smoking (OR 3.09, 95%CI 1.31–7.27, p = 0.010) were the independent predictors for identifying subjects with mPAP≥30 mmHg at HA. Moreover, FEF25% at LA was linearly correlated with mPAP at HA (r = -0.31, p < 0.001), which mainly existed in smokers. Compared to subjects with FEF25% ≥7.55 L/sec at LA, those with FEF25% <7.55 L/sec at LA showed higher levels of mPAP, and total PVR, and a multivariable OR of 11.16 (95%CI, 3.48–35.81) for developing mPAP ≥ 30 mmHg at HA. However, there was no significant difference in the incidences of AMS and its related clinical symptoms in subjects with different levels of FEF25%. Conclusions: Thus, these findings suggest that subjects with low FEF25% values at LA are susceptible to high levels of PAP at altitude but not the incidence of AMS following short-term HA exposure, especially in smokers.